Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Kue Bolu Bakar Pada Usaha Rumahan Ibu Yuli Di Desa Pepara Kecamatan Tanah Grogot - Muhammad Akbar; Syifi Fauziyah; Ratni Ratni (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The purpose of this research is to determine the simultaneous and partial influence as well as the dominant variables of the marketing mix consisting of Product (X1), Price (X2), Promotion (X3), Place (X4) on the Purchase Decision (Y) of Baked Bolu Cake in Mother's Home Business Yuli in Pepara Village, Tanah Grogot District. The sample in this study were consumers who coincidentally met the researcher during the research period to buy Bakar Bolu Cake at Mrs. Yuli's home business in Pepara Village, Tanah Grogot District from June to July 2023 with an incidental sampling technique and a sample size of 50 respondents. The results of the validity test calculation show that 28 statement items have a value of rcount > rtable, which means that all statements are considered valid, because rcount is greater than rtable. The results of the reliability test showed that a result of 0.944 was obtained, which means that the 28 questionnaire items were said to be reliable because Cronbach'alpha was > 0.6. The results of multiple linear analysis are Y= 1.117 + 0.308X1 + 0.042X2 + 0.283X3 + 0.175X4, meaning that the marketing mix variables have a positive effect on purchasing decisions. The correlation coefficient (R) value is 0.898 which is in the range of 0.80-1.000, meaning this number shows a very strong relationship between the variables Product (X1), Price (X2), Promotion (X3), Place (X4) on Purchasing Decisions ( Y). The value of the Adjusted R Square Determination Coefficient of 0.790 or 79.0% means that 79.0% of the purchasing decision variable (Y) is influenced by the variable factors Product (X1), Price (X2), Promotion (X3), Place (X4 ). The remaining 21% is influenced by other factors not examined in this research. The results of the f test calculation (simultaneous) show the value of fcount > ftable (47.080 > 2.58) which means that the marketing mix variables consisting of Product (X1), Price (X2), Promotion (X3), Place (X4) have a simultaneous effect or together on the Purchase Decision (Y) Bakar Bolu Cake at Mrs. Yuli's Home Business in Pepara Village, Tanah Grogot District. The results of the t test calculation (partial) by looking at this t calculate each marketing mix variable consisting of Product (X1), Price (X2), Promotion (X3), Place (X4) with a t test result of 3.318; 0.311; 2.465; and 2.614 which, when compared with the ttable value of 2.014, means that the dominant influence on purchasing decisions is Product (X1) because the Product variable (X1) has the highest value, namely 3.318 > 2.014. From the conclusion of the t test results obtained, the second hypothesis is that it is suspected that the Product variable (X1) has a dominant influence on the Purchasing Decision (Y) of Bakar Bolu Cake can be accepted or H0 is rejected Ha is accepted.